THE EFFECT OF USING VISUAL-PICTURE SEQUENCES TOWARDS STUDENTS’ ABILITY IN ENGLISH WRITING DESCRIPTIVE TEXT - Wika Hafsari M. Lubis; Yulia Sari Harahap (Sekolah Tinggi Pariwisata Mataram, 2022)
This research is aimed to find out the effect of using visual-picture sequences towards students’ ability in English writing descriptive text at the eighth grade students of SMP Islam Al-Ulum Terpadu in the academic year of 2022/2023. In this research, the researcher took two classes as the sample with their parallel classes and there were 60 students. Each class consists of 30 students and the entire population is taken as a sample then, divided into two groups. The instrument used in this thesis was an essay test. In collecting the data, the writer used pre-test and post-test. Before conducting post-test, the writer gave treatment. After getting enough data, the researcher calculated the data using ttest. Based on the computation, the mean score of pre-test in control group is 38 and the mean of post-test is 63. Meanwhile the mean score of pre-test in experimental group is 57 and the mean of post-test is 85. The results showed that the observed t was higher than the table value 2.5 > 1.67 at a significant level of 0.05 and the degree of freedom (df) was 58. The null hypothesis was rejected and the alternative was accepted. So, it can be stated that the hypothesis “the use of picture in teaching writing of descriptive text at the eighth grade students of SMP Islam Al-Ulum Terpadu in the academic year of 2022/2023 is accepted”. Based on the result finding, it can be concluded that the data presented is there is an effectiveness of using visual-picture sequences towards students’ writing ability in English writing descriptive text. The researcher hopes that the result of this study will be useful for students and English teacher in education field. The English teacher should improve their competencies by improving their material mastery, making use of appropriate and interesting media, so, their students’ English ability will be developed.